Finite-element simulation of residual stresses induced by laser shock peening in TC4 samples structurally similar to a turbine blade - A. Kostina; M. Zhelnin; A. Vedernikova; M. Bartolomei; S. Swaroop (Fracture and Structural Integrity)
This study is devoted to the investigation of residual stresses distribution (RSD) in a TC4 sample treated with laser shock peening. The study placed special emphasis on analyzing the RSD at the part of the samples structurally similar to a turbine blade, which is more frequently subjected to damage during service according to the aircraft statistics. Results of simulation showed that low power density of 1.11 GWt/cm2 could not induce compressive residual stress on the surface of a treated object. Furthermore, increasing the overlapping of laser spots does not improve the situation and still fail to induce surface compressive residual stress at a laser intensity of 1.11 GWt/cm2. The compressive stresses occur only with the rise in power density. Reducing the spot size from 3 mm to 1 mm for the power density of 10 GWt/cm2 results in a 20% increase in the magnitude of compressive residual stress in the area of interest. Moreover, applying 35% overlapping further enhances this value. In addition to increasing the magnitude of residual stress, this approach also leads to a more homogeneous RSD of the treated material